Effect of water stress on seed quality of coriander (Coriandrum sativum L.) - M M Anwer, S N Saxena, R K Kakani, R Saxena (Journal of Spices and Aromatic Crops, 2010)
Twelve coriander (Coriandrum sativum) accessions comprising of released varieties, advancedbreeding material, regional and exotic collections were evaluated at Ajmer (Rajasthan) foreffect of water stress on seed quality parameters including total oil, essential oil, test weightand seed size. All the recorded parameters showed significant genotypic variation as well assignificant interaction of genotype with environment. Mid-term water stress did not haveadverse effect on the studied quality parameters while terminal water stress resulted inreduction in quality parameters in most of the accessions.